Mainstreaming Internal Migration in Law and Policy Frameworks in Bangladesh: Analysis of a Rights-Based Approach to a Wicked Policy Problem. (September 2022) - Alam, Shawkat; Endacott, Joanna
Internal migration presents many challenges for governmental coordination due to the extensive and immediate action required to address this problem. However, it also poses opportunities regarding education, employment and living conditions, if the government creates pull factors to distribute migration away from primary to secondary cities. This process will require a rights-based approach, whereby the rights of internal migrants are mainstreamed in government planning to enable sustainable migration to Bangladesh's secondary cities. In this paper, the current international human rights and internal migration laws will be analysed, alongside the domestic laws and policies relevant to internal migration in Bangladesh. In doing so, this paper will explore how government policy and action can employ a rights-based approach to incorporate internal migration within the government's overarching development framework. A rights-based approach is necessary to effectively prepare for, and adapt to, the increase in internal migration in an equitable way.